2019
DOI: 10.1002/acr.23810
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Hyperlipidemia Among Patients With Rheumatoid Arthritis in the United States

Abstract: Objective. To determine the proportion of primary lipid screening among patients with rheumatoid arthritis (RA) and compare it with those among patients with diabetes mellitus (DM) and patients with neither RA nor DM, and to assess whether primary lipid screening varied according to the health care provider (rheumatologist versus nonrheumatologist).Methods. We analyzed claims data from US private and public health plans from 2006-2010. Eligibility requirements included continuous medical and pharmacy coverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our findings suggest that engaging PCPs may yield the higher probability of achieving lipid testing as PCPs thought of this process as lying within their scope of practice. This is consistent with previous studies that demonstrated that screening was 55% higher in patients with RA who visited a PCP vs. visiting a rheumatologist only [9]. Patients with RA may want to engage in discussions with their rheumatologist about lipid testing due to the frequency of visits with the rheumatologist as part of RA medication surveillance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings suggest that engaging PCPs may yield the higher probability of achieving lipid testing as PCPs thought of this process as lying within their scope of practice. This is consistent with previous studies that demonstrated that screening was 55% higher in patients with RA who visited a PCP vs. visiting a rheumatologist only [9]. Patients with RA may want to engage in discussions with their rheumatologist about lipid testing due to the frequency of visits with the rheumatologist as part of RA medication surveillance.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, ours and others' previous work have shown that lipid assessment among patients with RA is as low as 37% [9][10][11]. Although the likelihood of cholesterol testing increases if patients are followed by both primary care providers (PCP) and rheumatologists [9,10], some RA patients do not see a PCP, decreasing the likelihood of cholesterol testing [9][10][11].…”
Section: Introductionmentioning
confidence: 69%
“…In addition, the “lipid paradox” [ 61 ] may make it difficult to interpret lipid values in RA patients, as they can be lower during active RA and increase with effective treatment. A practical consideration is that many RA patients have not had lipids tested recently, and co-management with primary care physicians may be needed to improve rates of screening for hyperlipidemia [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In RA, co-management with a primary care physician improves screening for hyperlipidaemia. 41 Alternative care delivery models that use case managers and multidisciplinary teams have been tested with heterogenous results in the general population. 42 Limitations of this study include the inability to adjust for health behaviours and sociodemographics, which may result in unmeasured confounding.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%